(untitled) (Third Sector Social Economic Review, 2025)
This paper explores the profound influence of herd psychology on financial markets, emphasizing the cognitive biases that drive such behavior, such as the presence heuristic, fixation, confirmation bias, and overconfidence. By analyzing the responses of 300 financial sector employees, the study sheds light on the demographic and investment patterns that correlate with susceptibility to herd psychology. Key findings highlight that while a significant proportion of the respondents have a background in finance, their educational achievements do not necessarily correlate with a reduction in cognitive biases like over-optimism or loss aversion. Significantly, the research identifies correlations between specific investment behaviors and psychological traits: investors in real estate demonstrate more excessive optimism and conservatism compared to those investing in traditional bank deposits. These insights suggest that not only does herd psychology influence market dynamics by exacerbating trends and volatilities, but it also manifests distinctly across different investor profiles and investment instruments. The survey results reveal that 51.7% of the respondents are male, 57.7% have an education in finance and 18.7% invest in equities. The survey also revealed that 17.3% of the respondents do not follow market developments, while 21.7% of the respondents follow market developments on a monthly basis. Student’s t-test reveals that investors with financial education are more overconfident (p<0.05).